Perilaku Vektor Malaria Anopheles farauti Laveran (Diptera: Culicidae) Di Ekosistem Pantai (Kabupaten Biak Numfor) Dan Ekosistem Rawa (Kabupaten Asmat) Propinsi Papua - Kawulur, Hanna; Soesilohadi, RC Hidayat; Hadisusanto, Suwarno; Trisyono, Andi (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2015)
Biak Numfor and Asmat districts reported as malaria endemic areas in Papua (Papua Global Fund, 2011). Anopheles farauti mosquito is one of the malaria vectors in the region. Malaria control efforts have been made but there are still many cases of malaria. Malaria control will provide maximum results if there is a match between the vector behavior and programs undertaken. The purpose of this study was to determine the bionomics factors (behavioral) of malaria vector An. farauti mosquitoes in coastal ecosystems (Biak Numfor) and swamp (Asmat); namely: (a). density (b) age and (c) blood-seeking behavior. The method used in this study is human landing collection, resting collection and ELISA blood-feed. The results showed that the population density of An. farauti mosquito did not have a positive relationship with the number of malaria patients in both study areas. The activity of An. farauti mosquito on blood-seeking at the coastal and swamp ecosystems lasted all night but mainly at 18:00 to 19:00 hour. The study also showed that blood-seeking activity mostly done outside of the house. Age estimation of An. farauti mosquito population at coastal ecosystems ranging from 16-18 days, while in the swamp ecosystem is 12-14 days. Population density, approximately age and blood-seeking behavior indicates that An. farauti mosquitoes on the coastal and swamp ecosystems have the potential to be an effective malaria vector. Â Keywords: Malaria, Vector, Behavior